Quality protocols for nemarioc-AL and nemafric-BL phytonematicides and potential chemical residues in tomato fruits - Shadung, Kagiso Given (University of Limpopo, 2016)
Refer to document
Thesis (Ph. D. (Plant Production)) -- University of Limpopo,2016
Keywords: Nemafric-BL phytonematicides; Nemarioc-AL phytonematicides; Tomato fruits; Chemical residues; Food biotechnology -- South Africa; Canned tomatoes -- South Africa